Relación entre el nivel de conocimiento y la actitud sexual ligada al VIH/SIDA en estudiantes del 5to año de secundaria de la institución educativa “Juan Jiménez Pimentel” Tarapoto. Julio - Setiembre 2012 - Lázaro Murrieta, Ana Mariela (2012)
The present study aimed to determine the relationship between the level of sexual knowledge and attitudes related to HIV / AIDS in 5th year students of Junior High School "Juan Jimenez Pimentel" Tarapoto July – September 2012. The study is descriptive, correlational, and cross-cutting. Sample was taken as 58 students of the 5th year of secondary school Jiménez Juan Pimentel. Questionnaires were applied in the area of knowledge, sexual attitudes linked to HIV / AIDS. We identified the knowledge level (high, medium and low), attitudes (favorable and unfavorable). For the analysis we used descriptive statistics, means and standard deviations for the variables. The statistical verification, spoke with the results of the Pearson correlation, r = 0.794 (high correlation) and the testing of the hypothesis with the Student-t distribution, significance 0.05.Among the results, we can say that: The average age is 16.3 years, students who participated in the research, and the sex distribution is 57% female and 43% male. 79% of students in the 5th year of secondary educational institution Jiménez Juan Pimentel have average knowledge level about HIV / AIDS. 97% of students in the 5th year of secondary educational institution Jiménez Juan Pimentel have a PRO sexual attitude to HIV / AIDS. There is a statistically significant relationship between the level of sexual knowledge and attitudes related to HIV / AIDS in students.